The Proportion and Radiological Features of Pneumoconiosis in Workers Exposed to Dust in The Workplace - Mukhtar Ikhsan (Jurnal Respirologi Indonesia, 2019)
Background: One of the most common occupational diseases found in workplace is pneumoconiosis. The most disease is silicosis, which is lung disease caused by inhalation of dust containing free crystalline silica which afflicts tens of millions of workers in hazardous work and kill thousands of people worldwide. This study aimed to determine proportion and radiologic appearance of pneumoconiosis in workers exposed to dust in various industrial and mining processes. Method: This research used cross-sectional desaign, was conducted 2017 until September 2019 for various industrial and mining workers exposed to dust. Chest X-ray with digital radiography was read in International Classification of Pneumoconiosis Radiography from ILO version 2011, by a lung specialist who certified by The International Labor Organization (ILO) and The Asian Intensive Reader of Pneumoconiosis Project (AIR Pneumo). Results: ILO chest X-ray readings were carried out on 810 chest photos. Various radiological features of pneumoconiosis were obtained in 132 chest X-rays (16.2%), mostly abnormalities in parenchyma 87.1%. Parenchymal abnormalities are mostly of small round (p/p) with a profusion of 0/1 (89.6%). The most zones were lower right (58.1%). Pleural disorders (2%) mostly of costophrenic sinus obliteration 64.8%. Other disorders were 61/810 (7.24%), mostly of diaphragm abnormalities 15/61 (27.9%). Relevant appearance with pulmonary tuberculosis (infiltrates) was 8/810 (0.9%). Conclusion: The proportion of pneumoconiosis was 16.2%, mostly of parenchymal abnormalities (87.1%). Parenchymal abnormalities that occured still in the early phase, most zones were lower right (58.1%), pleural disorders 2%, other abnormalities were 7.24% and those that relevant to pulmonary tuberculosis 0.9%. (J Respir Indo. 2019; 39(4): 266-71)